Unternehmensfinanzierung, Unternehmensrechtsform und Besteuerung - Maiterth, Ralf; Sureth-Sloane, Caren

Steuerreformen und Übergangsprobleme bei Beteiligungsinvestitionen - Sureth-Sloane, Caren

Steuerliche und finanzwirtschaftliche Aspekte bei der Gestaltung von Genussrechten und stillen Beteiligungen als Mitarbeiterkapitalbeteiligungen - Sureth-Sloane, Caren; Halberstadt, Alexander

DTD-Driven Structure Preserving XML Compression - Böttcher, Stefan; Steinmetz, Rita (Flexible and Efficient Information Handling, 23rd British National Conference on Databases, BNCOD 23)

Finding the Leak: A Privacy Audit System for Sensitive XML Databases - Böttcher, Stefan; Steinmetz, Rita (22nd International Conference on Data Engineering Workshops (ICDEW'06))

Information Disclosure by XPath Queries - Böttcher, Stefan; Steinmetz, Rita (Secure Data Management, Third VLDB Workshop, SDM 2006)

Integrating instance-based learning and logistic regression - Hüllermeier, Eyke (In Proceedings IPMU-2006 11th International Conference on Information Processing and Management of Uncertainty in Knowledge-Based Systems, Paris, France)

The Choquet integral as an aggregation operator in case-based learning - Hüllermeier, Eyke (in Proceeding of the International Conference on Computational Intelligence, 9th Fuzzy Days, Dortmund)

A systematic approach to the assessment of fuzzy association rules - Dubois, D.; Hüllermeier, Eyke; Prade, H. (Data Mining and Knowledge Discovery)

Fuzzy methods in case-based recommendation and decision support - Dubois, D.; Hüllermeier, Eyke; Prade, H. (Journal of Intelligent Information Systems)

Learning from ambiguously labeled examples - Hüllermeier, Eyke; Beringer, J. (Intelligent Data Analysis)

Physicochemical descriptors to discriminate protein interactions in permanent and transient complexes by means of machine learning algorithms - Block, P.; Paern, J.; Hüllermeier, Eyke; Sanschagrin, P.; Sotriffer, C.; Klebe, G. (Proteins: Structure, Function and Bioinformatics)

From the similarity analysis of protein cavities to the functional classification of protein families using Cavbase - Kuhn, D.; Weskamp, N.; Schmitt, S.; Hüllermeier, Eyke; Klebe, G. (Journal of Molecular Biology)

Online clustering of parallel data streams - Beringer, J.; Hüllermeier, Eyke (Data and Knowledge Engineering)

A fuzzy-probablistic earthquake risk assessment system - Karimi, I.; Hüllermeier, Eyke; Meskouris, K. (Soft Computing)

"Wir haben ein Gesetz...!" rechtliche Anmerkungen zum Strafverfahren gegen Jesus - Krimphove, Dieter

Production engineering for video based e- and m-learning content - Herzog, Michael A.; Trier, Matthias; Sieck, Jürgen (Proceedings of UNESCO International Centre for Engineering Education (UICEE) 10th Baltic Seminar on Engineering Education)

Towards a Social Network Intelligence Tool for visual Analysis of Virtual Communication Networks - Trier, Matthias (Virtuelle Organisationen und Neue Medien)

Erratum to „Reductions of Symmetry configurations n3 - Boben, Marco; Pisanski, Tomaž; Ravnik, Natasa; Steffen, Eckhard (Discrete Applied Mathematics)

Executing Hardware Tasks on Dynamically Reconfigurable Devices under Real-time Conditions - Danne, Klaus; Mühlenbernd, Roland; Platzner, Marco (Proceedings of the 16th International Conference on Field Programmable Logic and Applications (FPL))

An EDF Schedulability Test for Periodic Tasks on Reconfigurable Hardware Devices - Danne, Klaus; Platzner, Marco (In ACM SIGPLAN/SIGBED Conference on Languages, Compilers, and Tools for Embedded Systems (LCTES))

Partitioned Scheduling of Periodic Real-time Tasks onto Reconfigurable Hardware - Danne, Klaus; Platzner, Marco (Proceedings of the 13th Reconfigurable Architectures Workshop (RAW))

Experimental and theoretical evidence for a hydrogen stabilizedc(2×2)reconstruction of the P-rich InP(001) surface - Letzig, T.; Willig, F.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)

Clean and pyrrole-functionalized Si- and C-terminated SiC surfaces: First-principles calculations of geometry and energetics compared with LEED and XPS - Preuss, M.; Bechstedt, F.; Schmidt, Wolf Gero; Sochos, J.; Schröter, B.; Richter, W. (Physical Review B)

Organic molecule adsorption on solid surfaces: chemical bonding, mutual polarisation and dispersion interaction - Schmidt, Wolf Gero; Seino, K.; Preuss, M.; Hermann, A.; Ortmann, F.; Bechstedt, F. (Applied Physics A)

Adsorption of phenylglycine on copper: Density functional calculations - Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)

Structure, energetics, and vibrational spectra of perylene adsorbed on Si(001): First-principles calculations compared with STM and HREELS - Preuss, M.; Miotto, R.; Bechstedt, F.; Rada, T.; Richardson, N. V.; Schmidt, Wolf Gero (Physical Review B)

Strongly bonded water monomers on the ice Ih basal plane: Density-functional calculations - Thierfelder, C.; Hermann, A.; Schwerdtfeger, P.; Schmidt, Wolf Gero (Physical Review B)

Adsorption of water on chlorine-terminated Si(111) from first principles: Substrate-induced ordering versus intermolecular interactions - Biering, S.; Hermann, A.; Schmidt, Wolf Gero (Physical Review B)

Si(001) surface optical anisotropies induced by π-conjugated overlayers and oxidation - Schmidt, Wolf Gero; Hermann, A.; Fuchs, F.; Bechstedt, F. (Current Applied Physics)

Si(001) c(4×2)–p(2×2) surface phase transitions induced by electric fields and doping - Schmidt, Wolf Gero; Seino, K. (Current Applied Physics)

Ga-richGaAs(001)surface fromab initiocalculations: Atomic structure of the(4×6)and(6×6)reconstructions - Seino, K.; Schmidt, Wolf Gero; Ohtake, A. (Physical Review B)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Semiempirical van der Waals correction to the density functional description of solids and molecular structures - Ortmann, F.; Bechstedt, F.; Schmidt, Wolf Gero (Physical Review B)

Aus dem Englischen ins Italienische: M. Cohen, Wittgestein’s Beetle and Other Thought Experiments

Asmuth, Christoph, Interpretation – Transformation, Vandenhoeck&Ruprecht, Amsterdam - Ficara, Elena (Rivista di Filosofia)

Die Ontologie in der „Kritik der reinen Vernunft“ - Ficara, Elena

Comparison of Performance and Realization Effort of a Very Sparse Matrix Converter to a Voltage DC Link PWM Inverter with Active Front End - Round, Simon; Schafmeister, Frank; Kolar, Johann (IEEJ Transactions of the Institute of Electrical Engineers of Japan)

Transient peak currents in permanent magnet synchronous motors for symmetrical short circuits - Meyer, M.; Böcker, Joachim (International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2006. SPEEDAM 2006.)

Energy Management for an Onboard Storage System Based on Multi-Objective Optimization - Knoke, Tobias; Romaus, Christoph; Böcker, Joachim; Dell'Aere, Alessandro; Witting, Katrin (IECON 2006 - 32nd Annual Conference on IEEE Industrial Electronics)

Modelling and Control of a Multi-Mass Ultrasonic Motor for Airborne Applications - Wetzel, H.; Fröhleke, N.; Böcker, Joachim; Ouchouche, S.; Bezanere, D.; Cugnon, F. (IECON 2006 - 32nd Annual Conference on IEEE Industrial Electronics)

Self-Optimization as a Framework for Advanced Control Systems - Böcker, Joachim; Schulz, Bernd; Knoke, Tobias; Fröhleke, Norbert (IECON 2006 - 32nd Annual Conference on IEEE Industrial Electronics)

Investigation of Power Supplies for a Piezoelectric Brake Actuator in Aircrafts - Li, Rongyuan; Fröhleke, Norbert; Wetzel, Hermann; Böcker, Joachim (2006 CES/IEEE 5th International Power Electronics and Motion Control Conference)

High Efficient 3kW Three-Stage Power Supply - Wetzel, H.; Fröhleke, N.; Böcker, Joachim; Ide, P. (Twenty-First Annual IEEE Applied Power Electronics Conference and Exposition, 2006. APEC '06.)

Advanced convoy control strategy for autonomously driven railway vehicles - Henke, C.; Fröhleke, Norbert; Böcker, Joachim (2006 IEEE Intelligent Transportation Systems Conference)

Drive Control and Position Measurement of RailCab Vehicles Driven by Linear Motors - Pottharst, A.; Henke, C.; Schneider, T.; Böcker, Joachim; Grotstollen, H. (Int. Symposium on Instrumentation and Control Technology (ISICT), Beijing, China)

Redundante Positionserfassung für ein spurgeführtes linearmotorgetriebenes Bahnfahrzeug - Schneider, T.; Schulz, B.; Henke, C.; Böcker, Joachim (Workshop Entwurf mechatronischer Systeme, Heinz-Nixdorf-Institut, Universität Paderborn,)

Optimum Control for Interior Permanent Magnet Synchronous Motors (IPMSM) in Constant Torque and Flux Weakening Range - Meyer, Michael; Böcker, Joachim (2006 12th International Power Electronics and Motion Control Conference)

Psychologism and the Distinction between Discovery and Justification - Peckhaus, Volker (Revisiting Discovery and Justification. Historical and Philosophical Perspectives on the Context Distinction)

Der Baum der Erkenntnis - Peckhaus, Volker (Die besten Nebenrollen. 50 Porträts biblischer Randfiguren)

Predeductive Reasoning - Peckhaus, Volker (Demonstrative and Non-demonstrative Reasoning in Mathematics and Natural Sciences. Workshop University of Rome ‘La Sapienza’, Rome, Villa Mirafiori, 16-17 June 2005)

Die Aktualität der Logik als Organon - Peckhaus, Volker (Kreativität. XX. Deutscher Kongress für Philosophie. 26.–30. September 2005 an der Technischen Universität Berlin. Kolloquiumsbeiträge)

Preface - Peckhaus, Volker; Löwe, Benedikt; Räsch, Thoralf (Foundations of Formal Sciences IV. The History of the Concept of Formal Sciences)

Rankings und Evaluationen im Bildungsbereich. - Lück, Sonja; Kraft, Manfred (Genus oeconomicum. Ökonomie - Macht - Geschlechterverhältnisse)

Husserl, Edmund, "Philosophy of Arithmetik. Psychological and Logical Investigations with Supplementary Texts from 1887-1901", übers. u. hg. v. Dallas Willard, Kluwer: Dordrecht 2003 (Collected Works, Bd. 10) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Copeland, B. Jack, "The Essential Turing. Seminal Writings in Computing, Logic, Philosophy, Artificial Intelligence, and Artificial Life plus ‘The Secrets of Enigma’", Clarendon Press: Oxford 2004 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Briefe an František Príhonský (1824–1948)", 3 Bde., hg. v. Jan Berg (Bernard-Bolzano-Gesamtausgabe, R. III, 3, 1–3), Frommann-Holzboog: Stuttgart-Bad Cannstatt 2005 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Vermischte Mathematische Schriften 1832–1848, Teil 1", hg. v. Jan Berg (Bernard-Bolzano-Gesamtausgabe, R. II.A.11.1), Friedrich Frommann Verlag-Günther Holzboog: Stuttgart-Bad Cannstatt 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Cassini, Alejandro, “Newton and Leibniz on Non-substantial Space”, In: Theoria. Segunda Epoca 20, Nr. 52 (2005), 25-42 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Lacki, Jan, “Styles of Physical Thinking Versus Mathematical Ones”, In: Synthese 134 (2003), 273-288 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Burgess, John P., “Mathematics and the Bleak House”, In: Philosophia Mathematics (3) 12 (2004), 18-36 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Burgess, John P, "Fixing Frege", Princeton University Press: Princeton, NJ 2005 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Floyd, Juliet/Shieh, Sanford (Hgg.), "Future Pasts. The Analytic Tradition in Twentieth-Century Philosophy. Dedicated to Burton Dreben", Oxford University Press: Oxford 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Stöltzner, Michael, “On Optimism and Opportunism in Applied Mathematics. Mark Wilson meets John von Neumann on Mathematical Ontology”, In: Erkenntnis 69 (2004), 121–143 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Weigel, Erhard, "Universi corporis pansophici caput summum. Werke I", hg. u. eingel. v. Thomas Behme, Frommann-Holzboog: Stuttgart-Bad Cannstatt 2003 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

van Dalen, Dirk, "Mystic, Geometer, and Intuitionist. The Life of L.E.J. Brouwer, Vol. 2: Hope and Disillusion", Oxford University Press: Oxford 2005 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hoffmann, Sarah, “Kitcher, Ideal Agents, and Fictionalism”, In: Philosophia Mathematica (3) 12 (2004), 3–17 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Weiner, Joan, "Frege Explained. From Arithmetic to Analytic Philosophy", Open Court: Chicago, IL 2004 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Gezielt fördern. Verben, Präpositionen, Adverbien, Konjunktionen. Arbeitsheft 5./6 - Breitkopf, Kathleen; Heinz, Hans Joachim; Niederhaus, Constanze; Plieninger, Martin

Martin, Donald A., “Gödel’s Conceptual Realism”, In: Bulletin of Symbolic Logic 11 (2005), 207–224 - Peckhaus, Volker (Mathematical Reviews)

Ehrlich, Philip, “The Rise of non-Archimedean Mathematics and the Roots of a Misconception. I. The Emergence of non-Archimedean Systems of Magnitudes”, In: Archives of the History of Exact Science 60 (2006), 1–121 - Peckhaus, Volker (Mathematical Reviews)

Tapp, Christian, "Kardinalität und Kardinäle. Wissenschaftshistorische Aufarbeitung der Korrespondenz zwischen Georg Cantor und katholischen Theologen seiner Zeit", Steiner: Stuttgart 2005 - Peckhaus, Volker (Mathematical Reviews)

Ewald, William, “Hilbert’s Wide Program”, in: Logic Colloquium 2000, Association for Symbolic Logic: Urbana 2005 (Lect. Notes Logic; 19), 228–251 - Peckhaus, Volker (Mathematical Reviews)

Eder, Ulrike: ,Auf die mehrere Ausbreitung der teutschen Sprache soll fürgedacht werden’: Deutsch als Fremd- und Zweitsprache im Unterrichtssystem der Donaumonarchie zur Regierungszeit Maria Theresias und Josephs II - Ptashnyk, Stefaniya (Studia Linguistica, Heft XXXI/2012. Wroclaw: Wydawnictwo Uniwersytetu Wroclawskiego)

Eder, Ulrike: „Auf die mehrere Ausbreitung der teutschen Sprache soll fürgedacht werden“: Deutsch als Fremd- und Zweitsprache im Unterrichtssystem der Donaumonarchie zur Regierungszeit Maria Theresias und Josephs II - Ptashnyk, Stefaniya (Studia Linguistica XXXI, Wroclaw 2012)

Quasiparticle corrections to the electronic properties of anion vacancies at GaAs(110) and InP(110) - Hedström, Magnus; Schindlmayr, Arno; Schwarz, Günther; Scheffler, Matthias (Physical Review Letters)
We propose a new method for calculating optical defect levels and thermodynamic charge-transition levels of point defects in semiconductors, which includes quasiparticle corrections to the Kohn-Sham eigenvalues of density-functional theory. Its applicability is demonstrated for anion vacancies at the (110) surfaces of III–V semiconductors. We find the (+/0) charge-transition level to be 0.49 eV above the surface valence-band maximum for GaAs(110) and 0.82 eV for InP(110). The results show a clear improvement over the local-density approximation and agree closely with an experimental analysis.

Elimination of the linearization error in GW calculations based on the linearized augmented-plane-wave method - Friedrich, Christoph; Schindlmayr, Arno; Blügel, Stefan; Kotani, Takao (Physical Review B)
This paper investigates the influence of the basis set on the GW self-energy correction in the full-potential linearized augmented-plane-wave (LAPW) approach and similar linearized all-electron methods. A systematic improvement is achieved by including local orbitals that are defined as second and higher energy derivatives of solutions to the radial scalar-relativistic Dirac equation and thus constitute a natural extension of the LAPW basis set. Within this approach linearization errors can be eliminated, and the basis set becomes complete. While the exchange contribution to the self-energy is little affected by the increased basis-set flexibility, the correlation contribution benefits from the better description of the unoccupied states, as do the quasiparticle energies. The resulting band gaps remain relatively unaffected, however; for Si we find an increase of 0.03 eV.

Dynamische Basisontologie und kooperative Semantiken. Möglichkeiten und Grenzen der Kombination begrifflicher und graphischer Wissensorganisation - Hagengruber, Ruth (HNI Jahresbericht)

Dynamic Ontology and Cooperative Semantics. The Combination of Conceptual and Graphical Knowledge Representation: Its Possibilities and Limits - Hagengruber, Ruth (HNI Annual Report)

Das Leseplakat. Eine Aufgabenstellung zur Rezeption vorgelesener Bücher - Kruse, Iris (Selbsttätigkeit und Aufgabenstellungen in der Grundschule. Grundschulunterricht)

Unterrichtliche Förderung auf der semantisch-lexikalischen Sprachebene: Didaktische Implikationen einer epigenetischen Entwicklungstheorie - Albers, Timm (Heilpädagogik Online)

Informelle Lernkontexte in der schulischen Sprachförderung - Albers, Timm; Mußmann, Jörg (Rundbrief der dgs Landesgruppe Niedersachsen)

Tiere in Afrika: Förderung semantisch-lexikalischer Sprachkompetenzen im Unterricht - Albers, Timm (Zeitschrift für Heilpädagogik)
Keywords: s2n; Scan2Net

Denken in Darstellungen – Schiller und die Geschichte - Süßmann, Johannes (Schiller und die Geschichte)

[Art.] Geschichtswissenschaft - Süßmann, Johannes (Enzyklopädie der Neuzeit, Bd. 4)

Fallstudien. Theorie – Geschichte – Methode. Internationale Konferenz (gefördert von der DFG). Bericht zur Tagung. Frankfurt am Main, 15.–17. September 2005 - Engel, Gisela; Scholz, Susanne; Süßmann, Johannes
Keywords: Fallgeschichte

Veränderung der Schulfreude von der Grundschule zur weiterführenden Schule - Bloh, Bea; Schürer, Sina (Risikofaktoren kindlicher Entwicklung. Migration, leistungsbezogene Emotionen und der Übergang von der Grundschulzeit zu den weiterführenden Schulen.A.)

Wie Schülerinnen und Schüler den Wechsel von der Grundschule zur weiterführenden Schule erleben – ein Zwischenbericht. - van Ophuysen, Stefanie; Bloh, Bea; Schürer, Sina (Forum Schule)

Veränderung von Schülermerkmalen in der Übergangsphase von der Grundschule zur weiterführenden Schule - Bloh, Bea; van Ophuysen, Stefanie; Schürer, Sina

Die Schulformentscheidung aus Elternsicht. Eine Untersuchung der zur Ablehnung der Schulformempfehlung am Ende der Grundschulzeit - Bloh, Bea

Schulformentscheidung am Ende der Grundschulzeit: Warum Eltern die Empfehlung nicht wahrnehmen - Bloh, Bea; van Ophuysen, Stefanie

Das Erleben des Übergangs in Abhängigkeit der Schulformempfehlung - van Ophuysen, Stefanie; Bloh, Bea

Veränderung der Schulfreude von der Grundschule zur weiterführenden Schule - Bloh, Bea; Schürer, Sina (Risikofaktoren kindlicher Entwicklung. Migration, leistungsbezogene Emotionen und der Übergang von der Grundschulzeit zu den weiterführenden Schulen)

Übergangsgestaltung durch schulstufenübergreidende Lehrerkooperation - Schürer, Sina; Bloh, Bea; van Ophuysen, Stefanie (Professionelles Handeln in der Grundschule: Entwicklungslinien und Forschungsbefunde)

Sociolinguistic Implications of Narratology: Focalization and ‘Double Deixis’ in Conversational Storytelling - Mildorf, Jarmila (The Travelling Concept of Narrative)

Disenchanting the World, Enchanting the Reader: The Negotiation of Biochemistry in Sinclair Lewis’ 'Arrowsmith' - Mildorf, Jarmila (Magic, Science, Technology, and Literature)

Introduction - Seeber, Hans Ulrich; Mildorf, Jarmila; Windisch, Martin (Magic, Science, Technology, and Literature)

Book review: Alan Palmer (2004). Fictional Minds. Lincoln: University of Nebraska Press - Mildorf, Jarmila (Anglia)

Nachruf auf Clotilde Schlayer - Schönhärl, Korinna (George-Jahrbuch)

Efficient Control of Formation Flying Spacecraft - Dellnitz, M.; Junge, O.; Krishnamurthy, A.; Ober-Blöbaum, Sina; Padberg, K.; Preis, R. (Friedhelm Meyer auf der Heide and Burkhard Monien, editors, New Trends in Parallel & Distributed Computing)